UPAYA PENINGKATAN KETERAMPILAN BERMAIN KASTI MELALUI MODIFIKASI ALAT DAN PERATURAN PADA SISWA KELAS IV SD NEGERI 3 BATEALIT KABUPATEN JEPARA TAHUN AJARAN 2012/2013 (Department of Physical Education, Sport, Health and Recreation, 2014)
Problems in this study is “How is the effort to improve skills through playing baseballequipment modification and regulation in grade IV Jepara 3 Batealit SDNAca-demic Year 2012/2013? “Method in this study is a class act with the procedures of planning, implementation,observation, and reflection. Subjects were fourth grade students of SD Negeri3 Batealit and a collaborator that Riyono Praise, S.Pd teacher in elementaryschool Penjasorkes 4 Raguklampitan Batealit Jepara regency. Fourth gradestudents num-bering 12 students consisting of 7 boys and 5 girls. In this study,using a modified tool and regulations.In the first cycle, the authors apply the modified equipment and rules baseballgame, of 12 students there are 8 students who have reached a level of mastery and4 stu-dents not yet complete. In the second cycle is 12 students turned out all thestudents were able to achieve mastery with 100% percentage of completeness.The modification of tools and regulations to improve the skills and student learningoutcomes in the game of baseball. Some researchers suggest, among others, 1)Students should pay attention to the explanation given by the teacher. 2) Teachersfurther develop creativity in teaching.